Application of Creative and Innovative Methods in Art Lessons at General Secondary Education - Aminova Sabina Anvar qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article focuses on the use of creative and innovative methods in art lessons in general secondary education to enhance students’ creative and aesthetic abilities. The study analyzes the effectiveness of interactive approaches, project-based learning, flipped classroom technology, and modern technological tools in increasing students’ engagement and developing their creative thinking skills. The article also provides recommendations for the practical implementation of these pedagogical approaches to improve the quality of art education.